6 - Médias, contestations et mouvements populaires au Sénégal de 2000 à 2012 - Samb, Moustapha (Africa Development, 2017)
This text addresses questions related to the discrepancy between the election promises of the power of alternation in 2000 and the feeling of dissatisfaction experienced by a good part of the population, especially young people from certain disadvantaged neighborhoods of the capital (Dakar) and some regions in the country (Senegal). This bitter disappointment resulted to the emergence of spontaneous protest movements and self-defense groups in demanding for local government to respect its commitments and to put an end to people’s sufferings. Within this context, the press played an important companionship role in these aspirations, which created misunderstandings between government authorities and the press during the first years of transformation in Senegal.